MANAJEMEN STRATEGIK DALAM SISTEM PENDIDIKAN: STUDI KASUS UPTD SD NEGERI JILATAN ALUR - Siti Mulkaf Lailawati; Ahmad Suriansyah; Ratna Purwanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Strategic management is an important approach to improving the effectiveness of education governance, especially in resource-constrained schools. This study aims to analyze the implementation of strategic management in UPTD SD Negeri Jilatan Alur in the context of primary schools in remote areas. The method used is a qualitative approach with a case study, through interviews, observations and document analysis of the principal, teachers and school committee. The results showed that despite not having a formal strategy document, the school carries out management intuitively through a culture of gotong royong and shared reflection. The conclusion of this study is that schools have great potential to implement education strategies more systematically if supported by training and active involvement of all stakeholders